1996
DOI: 10.1037/0021-843x.105.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Goal-relevant dimensions of hypochondriacal tendencies and their relation to symptom manifestation and psychological distress.

Abstract: A national sample of 60 male and 61 female adults completed a telephone interview that included measures of hypochondriacal tendencies, psychological distress, and symptom manifestation. They also provided cognitive evaluations for their most important health goal on scales measuring self-efficacy, value, planning, self-reward, self-criticism, self-monitoring, social comparison, and positive and negative goal-based arousal. Health goal cognition significantly predicted hypochondriacal tendencies measured 15 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 67 publications
1
17
0
1
Order By: Relevance
“…This finding is also consistent with previous-mostly cross-sectional-studies, where goal self-efficacy beliefs (Lecci et al, 1996;Meyer et al, 2004) and more general self-efficacy beliefs (Ormel et al, 1997;Penninx et al, 1998;Saltzman & Holahan, 2002) have been found to account for depressive symptoms. Kavanagh (1992) suggested that efficacy beliefs may affect mood more strongly when they are linked to a domain that is central to self-esteem.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is also consistent with previous-mostly cross-sectional-studies, where goal self-efficacy beliefs (Lecci et al, 1996;Meyer et al, 2004) and more general self-efficacy beliefs (Ormel et al, 1997;Penninx et al, 1998;Saltzman & Holahan, 2002) have been found to account for depressive symptoms. Kavanagh (1992) suggested that efficacy beliefs may affect mood more strongly when they are linked to a domain that is central to self-esteem.…”
Section: Discussionsupporting
confidence: 93%
“…Unfortunately, the majority of research on goal-related self-efficacy has been cross-sectional, and as such offers little evidence that goal cognitions constitute vulnerability factors rather than simply correlates of depressive symptoms (Doerfler & Aron, 1995;Karoly & Ruehlman, 1995;but cf. Karoly & Ruehlman, 1996;Lecci, Karoly, Briggs, & Kuhn, 1994;Lecci, Karoly, Ruehlman, & Lanyon, 1996;Meyer, Beevers, & Johnson, 2004;Pomaki, Maes, & ter Doest, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Those who recognized the change and reorganized their goals accordingly expressed significantly higher levels of life satisfaction than those who failed to recognize the change and failed to adapt their goals (cf. Affleck et al 1998;Karoly, 1999;Karoly & Ruehlman, 1995Lecci et al 1996).…”
Section: Principles Related To Goal Selection Based On Goal Expectancymentioning
confidence: 97%
“…Participants were asked to indicate if they had ever been diagnosed by a doctor as having any one of eleven common chronic illness categories, such as cancer, heart disease, and ''other'' (see Lecci, Karoly, Ruehlman, & Lanyon, 1996). The importance of emphasising a doctor's diagnosis is that confounds with hypochondriasis are minimised, as hypochondriacs might be more prone to think that they have a diagnosis.…”
Section: Diagnostic Checklistmentioning
confidence: 99%